Rough Work and Rugged Men: The Social Construction of Masculinity in Working-Class History - Maynard, Steven (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1989)
Abstract This paper uses two recent books in Canadian labour history, Craig Heron's Working in Steel and Ian Radforth's Bushworkers and Bosses, to briefly review the place of masculinity in working-class history. The author suggests that while Heron and Radforlh introduce masculinity into their studies, they do not fully develop all of its meanings and functions. Drawing upon the literature on the social construction of work, gender, and sexuality, the paper then goes on to suggest some ways in which we can begin to explore aspects of masculinity and sexuality within working-class history.